Assessment of Heavy Metal Bioaccumulation in Wild Fish ( Clarias gariepinus ) Consumed in Wukari Area of Taraba State, Nigeria (2017)
A study was carried out on the assessment of heavy metal bioaccumulation in wild fish (Clarias gariepinus) consumed in Wukari area of Taraba State in Nigeria between July and November 2016. Twenty-two (22) market sizes smoke-dried fish (C. gariepinus) were randomly bought from the Wukari markets in Taraba State in July 2016 and burned to ashes with a furnace at a temperature of 400°C for two hours and stored in sample bottles prior to acid digestion. Concentration of heavy metals (Cd, Pb, Cu, Ni, Mn and Co) in the dried fish samples was analyzed using Buck Scientific Atomic Absorption Spectrophotometer (AAS). The results showed that the mean concentration of highly toxic Cd and Pb was below the World Health Organization’s (WHO) guideline limits of 0.05 ppm and 1.0 ppm respectively. The essential Cu concentration in the liver (32 ppm) exceeded the WHO set limit of 30 ppm while the other organs were below it. Fifty percent (50%) of the organs (bones, liver and muscles) exceeded the WHO guideline limit of 0.07 ppm for Ni, while the gills, fins and skin were below it. The mean Mn concentration in all the organs were below the FEPA guideline limit. The results showed that the mean toxic heavy metal Cd and Pb in the organs of the fish C. gariepinus were below the World Health Organization (WHO) limit and therefore safe for human consumption. Essential heavy metals like Cu and Ni were slightly above WHO guideline limit in some organs which means consumption quantity should be in moderation. It is therefore recommended that regular biomonitoring studies on heavy metals should be carried out on fish species widely consumed in the area for public health good